The use of Na+ and K+ ion concentrations as potential diagnostic indicators of subclinical mastitis in dairy cows - Haron, Abd Wahid; Abdullah, Faez Firdaus Jesse; Tijjani, Abdulnasir; Abba, Yusuf; Adamu, Lawan; Mohammed, Konto; Mohammed Amir, Aisyah Munira; Sadiq, Mohammad Abubakar; Mohd Lila, Mohd Azmi (Veterinary World, 2014)
Aim: This study was conducted to evaluate the concentrations of sodium (Na+) and potassium (K+) ions in milk of lactating dairy cows with and without subclinical mastitis as putative indicators for detecting subclinical mastitis in dairy cows.